SELF PRESENTATION 4.0: STRATEGI PERSONAL BRANDING DI RUANG VIRTUAL - Pratiwi, Mutia Rahmi (Komuniti: Jurnal Komunikasi dan Teknologi Informasi, 2019)
Youtube is one of the popular social media for the younger generation. The results of research conducted by the Indonesian Economic Forum in 2018, Youtube is called the number one most active social media platform with a percentage of 43%. Youtube content presents music, videos, games, vlog content. This research explains the personal branding strategy through YouTube. From the beginning of its appearance until 2019, KIFLYF TV became a Youtube channel which has 1.5 million subscribers. The research method used is the Ethnographic Content analysis method, namely text analysis and interviews with KIFLYF TV members. The results showed that KIFLYF TV utilizes YouTube as a personal branding through self-presentation strategies, namely ingratiation, self-promotion, exemplification, supplementation. The specificity of content owned by KIFLYFTV begins with the use of tagline, the main characteristic of the concept is friendship and social media optimization that is owned by involving other YouTubers.